Perancangan Jaringan Fiber to the Home (FTTH) pada Perumahan di Daerah Urban - Sahid Ridho; A’isya Nur Aulia Yusuf; Syaniri Andra; Dinari Nikken Sulastrie Sirin; Catur Apriono (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2020)
The evolution of communication network comes from the need for users to stay connected anytime and anywhere. Modernization of the network continues to be done to increase bandwidth capacity in order to obtain an increase in multimedia services, especially in urban areas. Of various transmission media, optical fiber is the best choice to support reliable communication networks. One of the optical fiber communication technologies is Fiber to the Home (FTTH). This study proposes FTTH network design with Gigabit Capable Passive Optical Network (GPON) technology aimed at housing in urban areas. The design uses aerial and duct-aerial cabling sy stems. The design analysis is carried out based on the parameters of the link power budget, rise time, Bit Error Rate (BER), components and costs required. The value of the power budget link for the uplink and downlink are -22.792 dBm and -23.120 dBm. The rise time value for uplink and downlink are 0.256 ns and 0.258 ns, while the BER value is 14.628 x 10-12. The calculation results show that the design meets the required parameters, hence, the proposed network can be implemented. For the cost components required by the aerial system, it is 11.56% less than of the duct-aerial sistem.